2016
DOI: 10.1002/ijgo.12012
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of randomized controlled trials comparing hysteroscopic morcellation with resectoscopy for patients with endometrial lesions

Abstract: Hysteroscopic morcellation is associated with a higher operative success rate and a shorter operative time among patients with endometrial lesions than is resectoscopy. More high-quality trials are required to validate these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 24 publications
2
21
2
Order By: Relevance
“…In an office setting, patient acceptability and procedural pain were linked to the duration of hysteroscopic surgery 21–23 . Therefore, the reduction in the total operative time is of a high clinical significance for patient acceptability 24 . Seven (14.6%) women out of 48 of the BE group reported moderate pain (VAS score between 5 and 7).…”
Section: Discussionmentioning
confidence: 99%
“…In an office setting, patient acceptability and procedural pain were linked to the duration of hysteroscopic surgery 21–23 . Therefore, the reduction in the total operative time is of a high clinical significance for patient acceptability 24 . Seven (14.6%) women out of 48 of the BE group reported moderate pain (VAS score between 5 and 7).…”
Section: Discussionmentioning
confidence: 99%
“…Our results of the reduction in the operating time with hysteroscopic morcellation confirm the results of four previous RCTs and systematic reviews. [ 4 5 6 7 9 10 ] In hysteroscopic morcellation, the simultaneous cutting and aspiration of polyps may have reduced the number of the device's insertions and thus reduced the operating time.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that RFA of uterine myomas relieves the symptoms associated with myomas such as heavy bleeding and bulk-related symptoms [14]. However, to date there are no published studies that prospectively investigate patient follow-up after RFA treatment in terms of menstruation status and hysteroscopic results [15].…”
Section: Discussionmentioning
confidence: 99%